2017
DOI: 10.1097/ccm.0000000000002058
|View full text |Cite
|
Sign up to set email alerts
|

Point Prevalence Study of Mobilization Practices for Acute Respiratory Failure Patients in the United States

Abstract: Objective Early mobility in mechanically ventilated patients is safe, feasible, and may improve functional outcomes. We sought to determine the prevalence and character of mobility for intensive care unit (ICU) patients with acute respiratory failure in US ICUs. Design Two-day multicenter point prevalence study Patients Adult patients (≥ 18 years old) with acute respiratory failure requiring mechanical ventilation in 17 US hospitals and 42 ICUs. Interventions We defined therapist-provided mobility as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
132
5
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(165 citation statements)
references
References 28 publications
19
132
5
9
Order By: Relevance
“…(30, 31) A recent point-prevalence study across 42 United States ICUs reported 32% of adult patients with acute respiratory failure (and 26% of ventilated patients) received physical/occupational therapy. (32)An Indian survey reported higher mobilization levels(86% at the bed side, 70% to a wheel chair and 67% limited ambulation). (29)Our results suggest a discordance in intent and resources for mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…(30, 31) A recent point-prevalence study across 42 United States ICUs reported 32% of adult patients with acute respiratory failure (and 26% of ventilated patients) received physical/occupational therapy. (32)An Indian survey reported higher mobilization levels(86% at the bed side, 70% to a wheel chair and 67% limited ambulation). (29)Our results suggest a discordance in intent and resources for mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the nature of the intervention prevented blinding of the treating physician, which must be respected as a bias. Current real word practice regarding mobilization is as previously shown not meeting guideline recommendations . We considered it would nevertheless be unethical to perform anything less than protocol‐based physiotherapy, which is our clinical standard, in the control group.…”
Section: Limitationsmentioning
confidence: 99%
“…PM in this study referred to PM that was done on mechanically ventilated patient. PM was usually done by nurses for mechanically ventilated patient such as positioning patient from supine to left lateral, right lateral and prone or lifting patient with and sit patient up with bed on fowler or high fowler positions, perform suctioning with physiotherapist and Systemic reviews had shown early mobilization improved outcomes of mechanically ventilated patient [1,14] and decreases mechanical ventilation associate weakness [15]. The benefits of early mobilization include reduction in length of stay in ICU and hospital as well as improvements in strength and functional status [16,17].…”
Section: Background and Literature Reviewmentioning
confidence: 99%